Determinants of visitor expenditure at a major sports event - Malcolm Greig; Ronald W McQuaid (European Regional Science Association (ERSA), 2004)
This paper develops a model of the determinants of visitor expenditure at a one day repeated major sporting event in Edinburgh, Scotland. An econometric model is developed that combines both macroeconomic data and socio-economic information derived from over 1,000 visitor interviews. This allows us to control for individual characteristics and estimate the derived elasticities for the macroeconomic determinants of expenditure. The findings suggest that socio-economic characteristics of individuals may be more significant than macroeconomic indicators in explaining variations in visitor expenditure. Among individual characteristics, the region of origin, length of stay, type of accommodation, type of expenditure and personal income are associated with the level of per capita visitor expenditure. This should assist regional policy formulation in attracting higher spending visitors and thereby maximising the income and employment benefits from sporting events and other areas of tourism.
Keywords: 330